Consumer wants and use of ingredient and nutrition information for alcoholic drinks: A cross-cultural study in six EU countries. (January 2018) - Grunert, Klaus G.; Hieke, Sophie; Juhl, Hans Jørn
Highlights: We investigate consumer wants and use of ingredients and nutritional information for alcoholic drinks. An online survey indicates considerable differences between six European countries. Information wants and use are highest in Spain and lowest in Denmark and the Netherlands. Product involvement, health interest and previous knowledge all affect information wants and use. Product involvement is the main determinant of both information wants and use. Abstract: In the EU, alcoholic beverages are exempt from Regulation 1169/2011 on the provision of food information to consumers (FIC) that requires food labels to contain both ingredient information and information on key nutrients. We investigate to which extent consumers want and use information on ingredients and nutritional characteristics of alcoholic drinks from a range of off-label information sources. We also investigate how wants and use are affected by product involvement, health interest, and previous knowledge on ingredients and nutritional characteristics of alcoholic drinks. Data are collected by means of an online survey in six European countries (Denmark, n = 787; Germany, n = 993; Netherlands, n = 934; Poland, n = 1003; Spain, n = 810; UK, n = 868). Results of a Partial Least Squares analysis indicate that both information wants and information use are mainly determined by product involvement and to a lesser extent by health interest. Previous ingredient knowledge lowers information wants and use, whereas previous nutrition knowledge increases it. Average levels of information wants and use differ between the six countries, with the highest levels in Spain and the lowest in Denmark and the Netherlands. The results have implications for both marketers of alcoholic drinks and for policies regarding information provision.